Demography and Population Dynamics of a Small Mammal Assemblage in Chilean Semiarid Thorn‐Scrub Habitat: A 30‐Year Study - Kelt, Douglas A. (2025)
Characterizing population dynamics in heterogeneous environments requires comprehensive long-term data. We monitored seven small mammals in replicated sites in a semiarid Chilean thorn-scrub habitat over 30 years using monthly capture–mark–recapture (CMR) sampling. We applied a superpopulation CMR modeling framework to examine the following: (i) How do population sizes and demographic parameters vary seasonally and over time? and (ii) Are there commonalities in the variation of those parameters either seasonally or annually? Capture probabilities among four “core” species (Octodon degus, Phyllotis darwini, Abrothrix olivacea, and Thylamys elegans) varied strongly over time, as did apparent survival among years and rainfall seasons, with individuals generally experiencing higher survival during the wet season. Recruitment measures also showed strong annual and seasonal variation, with higher numbers in wet seasons and years. Capture probability in three “opportunistic” species (Abrocoma bennettii, Abrothrix longipilis, and Oligoryzomys longicaudatus) varied over time, as did survival and recruitment across rainfall or reproductive seasons. As predicted, annual and seasonal variation in rainfall strongly influenced the survival and recruitment of most species, and their populations increased rapidly following rainfall events. Unsurprisingly, core species shared similar overall responses to environmental drivers; opportunistic species responded differently to seasonal or annual variation in rainfall, perhaps reflecting their origins in non-thorn-scrub habitat. Finally, for all species, population size correlated more strongly with the number of recruits than with survival, suggesting that the former has a greater influence on the dynamics of our study populations. This study provides the first insight into the demography of the entire small mammal community at our study site, and in particular, the demography of A. bennettii, A. longipilis, and O. longicaudatus from semiarid habitat. Our results, based on the longest time series in South America, provide comprehensive demographic information on a diverse small mammal community, and offer novel insight into community-level response to changing climate.